2007
DOI: 10.1002/ijc.22563
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus‐16 DNA methylation patterns support a causal association of the virus with oral squamous cell carcinomas

Abstract: Infection with human papillomavirus-16 (HPV-16) is the cause of most anogenital carcinomas. This virus is also detected in about 20% of all head and neck squamous cell carcinomas. While there is strong evidence for a causal etiological role in the case of tonsillar carcinomas, causal association with malignant lesions of the oral cavity is not yet conclusive. Our previous investigations of HPV-16 DNA methylation in anogenital sites have identified hypermethylation of the L1 gene and part of the long control re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 35 publications
4
45
1
Order By: Relevance
“…During carcinogenesis, the process is progressively dysregulated, beginning at the earliest stages of neoplasia. Many HPV DNA methylation studies have focused on the viral long control region (LCR) and 3 0 terminus of the L1 open reading frame (ORF) and have generally reported that the LCR sites were minimally methylated in most lesions, whereas the L1 sites were methylated more frequently in ICC than premalignant lesions (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Other studies have reported an inverse relationship between elevated methylation in the E6 ORF and high-grade CIN (32,33).…”
Section: Introductionmentioning
confidence: 99%
“…During carcinogenesis, the process is progressively dysregulated, beginning at the earliest stages of neoplasia. Many HPV DNA methylation studies have focused on the viral long control region (LCR) and 3 0 terminus of the L1 open reading frame (ORF) and have generally reported that the LCR sites were minimally methylated in most lesions, whereas the L1 sites were methylated more frequently in ICC than premalignant lesions (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Other studies have reported an inverse relationship between elevated methylation in the E6 ORF and high-grade CIN (32,33).…”
Section: Introductionmentioning
confidence: 99%
“…Betel nut chewing has been implicated in oscc, leukoplakia and oral submucous fibrosis (progressive inflammation and fibrosis of connective tissue) (6). Other predisposing factors for oral cancer include alcohol use, gender, age and infection by human papillomavirus (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to cervical cancer, in which HPV has been established as a primary cause, oral cavity cancers are caused primarily by tobacco use, and high-risk HPV might be a cofactor for oral carcinogenesis [15,27] . Studies using squamous cell carcinoma samples suggest that high-risk HPV infection could interfere in epigenetic regulation [28] , specifically in the induction of the p16 CDKN2A gene methylation [12,23,29] .…”
Section: Analysis Ofmentioning
confidence: 99%
“…Recent evidence suggests that epigenetics is an important mechanism in oral carcinogenesis [12][13][14][15][16] . DNA methylation is the addition of methyl radicals to specific regions of DNA that predominantly contain cytosine nucleotides.…”
Section: Analysis Ofmentioning
confidence: 99%